2021
DOI: 10.37766/inplasy2021.12.0056
|View full text |Cite
|
Sign up to set email alerts
|

The Visceral Adiposity Index in Non-Alcoholic Fatty Liver Disease and Liver Fibrosis — Systematic Review and Meta-Analysis

Abstract: Review question / Objective: The objective of the study was to compare the mean difference and AUROC of Visceral Adiposity Index (VAI) in NAFLD/NASH/liver fibrosis patients and controls in observational studies. Condition being studied: Nonalcoholic fatty liver disease (NAFLD) is a multi-system disease, being mainly a liver pathology involving excessive hepatic fat accumulation unrelated to alcohol consumption or other secondary causes of hepatic steatosis. It is an emerging cause of concern and increasing cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Therefore, the disease treatment emphasizes the regulation of metabolism, but from clinical practice, there are still several bottlenecks in NAFLD from diagnosis to treatment [9]. Firstly, in terms of diagnosis, although there are more recognized and mature protocols for monitoring NAFLD in traditional high-risk groups (diabetes, hypertension, overweight), more and more studies have found that NAFLD occurs more frequently in people with normal BMI (i.e., visceral obesity) [49], and for such patients, especially in non-obese people with intermittent transaminase abnormalities, there is still a lack of su ciently effective biological markers for the diagnosis of NAFLD and a lack of effective protocols for predicting the risk of development, as liver aspiration biopsy is still not a common tool, and current guidelines only recommend regular follow-up, which is not conducive to timely treatment [50,51]. Secondly, according to the existing guideline recommendations, lifestyle changes, exercise, and diet control are important non-pharmacological options for people with established NAFLD [52].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the disease treatment emphasizes the regulation of metabolism, but from clinical practice, there are still several bottlenecks in NAFLD from diagnosis to treatment [9]. Firstly, in terms of diagnosis, although there are more recognized and mature protocols for monitoring NAFLD in traditional high-risk groups (diabetes, hypertension, overweight), more and more studies have found that NAFLD occurs more frequently in people with normal BMI (i.e., visceral obesity) [49], and for such patients, especially in non-obese people with intermittent transaminase abnormalities, there is still a lack of su ciently effective biological markers for the diagnosis of NAFLD and a lack of effective protocols for predicting the risk of development, as liver aspiration biopsy is still not a common tool, and current guidelines only recommend regular follow-up, which is not conducive to timely treatment [50,51]. Secondly, according to the existing guideline recommendations, lifestyle changes, exercise, and diet control are important non-pharmacological options for people with established NAFLD [52].…”
Section: Discussionmentioning
confidence: 99%
“…This systematic review and meta-analysis were written as per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 statement [ 24 ]. The study was registered in INPLASY (International Platform of Registered Systematic Review and Meta-analysis Protocols); registration number (INPLASY2021120056) [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…However, the NAFLD-LFS requires fasting serum insulin, which is not routinely available, hence limiting its clinical utility. Visceral adiposity index (VAI), which uses BMI, waist circumference, and serum triglyceride and high-density lipoprotein (HDL) cholesterol levels, is a surrogate biomarker of visceral adiposity, 16 and a recent systematic review and meta-analysis by Ismaiel et al 17 concluded that VAI has fair accuracy in diagnosing adult NAFLD with an AUROC of 0.77. In a head-to-head comparison with FLI, HSI, and NAFLD-LFS, using liver biopsy as reference standard, VAI performed best in detecting the presence of hepatic steatosis with an AUROC of 0.92.…”
Section: Non-invasive Assessment Of Hepatic Steatosismentioning
confidence: 99%